If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 3X + 2 Reorder the terms: Y = 2 + 3X Solving Y = 2 + 3X Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 2 + 3X
| 3(45)+x+6(45)+4x=180 | | 4xy+5xy-3xz-2xy+xy+3xz= | | 8x+6-9x=2-y-15 | | 8-10p+4+8p= | | z(3+2i)=iz+2 | | 2(x+5)+5=2x+9 | | 3x-250=2858 | | 2x+15=385/(x+1) | | 3x+54-3x+6x+4(54-3x)= | | (x+3)(x^2+2x+6)=0 | | 1/16x-3/4y=-1 | | 5b-3/3b-4b+1/5b | | .2y+.5x=4.05 | | 2/3n=-18 | | -12=.5x+x | | 3y+x=54 | | 2(x+8)=30+18 | | 3x+y=54 | | 4x+4x=50 | | -12=6+1y | | A=5H(b+B) | | 3(2x+8)=30+18 | | 5(11+7)=x | | 3x+y+6x+4y=180 | | x^2-12x+68=0 | | 16x-3[4x+7]=6x-[2x+21] | | 3x+x=372 | | z-7z=5z-3-z | | y^2-20=0 | | x^2-2x+10=58 | | 4v/v-3-3/v-3=7 | | -20+5=1 |